A Pedagogical Task is the Formation of the Professional Outlook of Future Teachers - Samadova Dilrabo Yusupovna (Peerian Journals Publishing, 2022)
Changes in society, modern requirements for professional knowledge, personal qualities of specialists have created the need to update the content of education, innovative forms and methods of teaching in higher educational institutions of pedagogy, and to widely introduce modern information technologies into practice. In this article, the author analyzes ways to improve the professional outlook of pedagogues.
Keywords: Teacher; education; students; curriculum